PENGARUH KOMPOSISI DAN FREKUENSI APLIKASI UREA DENGAN ARANG SEKAM PADI PADA PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Dwi Yulianayan Sari; Yonathan Parapasan; Rijadi Subiantoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Fertilizer can be used as a tool enchane plant growth and soil fertility, because by applying fertilizer it can supply nutrient in the soil so that plant growth is optimal. The type of fertilizer used is organic fertilizer (rice hust charcoal) and anrganic (urea) which acts as an increase in plant growth and devolopment and increase soil fertility. This study aims to obtain the effect of the composition of the application frequency of the mixture of urea and hust charcoal on the growth of cacao seeds, get the best effect of the composition of the urea fertilizer and husk charcoal on the growth of cacao seedling and get an interaction between the composition of the application frequency of urea and husk charcoal on the growth cacao seed. This research was carried out in the practice garden of the devolopment of plantation plant cultivation and Lampung State analysis laboratory. The study was conducted from January to May 2019. The study was arranged in a factorial block design (RBD) with 2 factor, the first factor composition fertilizer and second factor application frequency of urea and rice husk charcoal. The research showed there was on effect of the best composition of the mixture of urea dan husk charcoal on the growth of cacao seedling in the (1:2) with application frequency 2 time, and there was an interaction between the composition of the application frequency of urea and husk charcoal on the growth of cacao seedling in all observed variables except for abserving stem diameter, N plant tissue and plant sttover dry weight.